Small Firms in Regional Clusters: Local Networks and Internationalization in the Southern Hemisphere. (1st April 2019) - Felzensztein, Christian; Deans, Kenneth R.; Dana, Léo‐paul
Abstract : This paper reports on a three‐country comparative study examining the internationalization of family winemakers in distinct regional wine clusters of Argentina, Chile, and New Zealand. In‐depth interviews were conducted with owner–operators, to understand the drivers and barriers to internationalization of their businesses. Key findings reveal that while size and age are not determinants of the ability or propensity to export wine, the existence of an independent industry body has a positive impact and greatly speeds up the internationalization process, providing an effective route for small firms to establish their very often, relatively unknown brand(s) in lucrative foreign markets.